Cerebral Energy Status and Altered Metabolism in Early Brain Injury After Aneurysmal Subarachnoid Hemorrhage: A Prospective 31P-MRS Pilot Study - Treichl, Stephanie Alice; Ho, Wing Mann; Steiger, Ruth; Grams, Astrid Ellen; Rietzler, Andreas; Luger, Markus; Gizewski, Elke Ruth; Thomé, Claudius; Petr, Ondra (Frontiers in Neurology, 2022)
Background Acute changes of cerebral energy metabolism in early brain injury (EBI) after aneurysmal subarachnoid hemorrhage (aSAH) may play a crucial role for overall neurological outcome. However, direct detection of these alterations is limited. Phosphorous magnetic resonance spectroscopy (31P-MRS) is a molecular-based advanced neuroimaging technique allowing measurements of pathophysiological processes and tissue metabolism based on various phosphorous compound metabolites. This method may provide objective assessment of both primary and secondary changes. Objective The aim of this pilot study was to evaluate the feasibility and the diagnostic potential of early 31P-MRS in aSAH. Methods Patients with aSAH treated for ruptured aneurysms between July 2016 and October 2017 were prospectively included in the study. 3-Tesla-MRI including 31P-MRS was performed within the first 72 hours after hemorrhage. Data of the vascular territories of the anterior, middle and posterior cerebral arteries (ACA, MCA, PCA) and the basal ganglia were separately analyzed and compared with data of a healthy age- and sex-matched control group. Phosphorous compound metabolites were quantified, and ratios of these metabolites were further evaluated. Influence of treatment modality, clinical conditions, and analgosedation were analyzed. Results Data of 13 patients were analyzed. 31P-MRS showed significant changes in cerebral energy metabolism after aSAH in all cerebrovascular territories. Both PCr/ATP and PCr/Pi ratio were notably increased (P<0.001). Also, Pi/ATP was significantly decreased in all cerebrovascular territories (P=0.014). PME/PDE ratio was overall significant decreased (P<0.001). Conclusion: 31P-MRS is a promising non-invasive imaging tool for the assessment of changes in energy metabolism after aSAH. It allows a detailed insight into early brain injury and seems to harbor a high potential for clinical practice.